2013
DOI: 10.1093/fampra/cmt080
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for guideline implementation in primary care focusing on patients with cardiovascular disease: a systematic review

Abstract: The use of implementation strategies for the distribution of guidelines on CVD can be convincingly effective on physician adherence, regardless whether based on a unimodal or multimodal design. Three distinct strategies should be well considered in such an attempt: organizational changes in the primary care team, patient education and provider education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 55 publications
1
53
1
Order By: Relevance
“…Nineteen [73–91] ( n  = 470 studies) evaluated the impact of environmental restructuring including the use of collaborative or shared care practices or the institution of specialized nurses or other allied healthcare professionals [73, 74, 77–83, 85–91], or guideline implementation [75, 76] in primary healthcare settings. Evidence from poor- to high-quality reviews indicate organizational changes to increase collaboration among pharmacists, nurses, prevention coordinators, and other primary healthcare professionals led to increased physicians’ adherence to guidelines [75].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen [73–91] ( n  = 470 studies) evaluated the impact of environmental restructuring including the use of collaborative or shared care practices or the institution of specialized nurses or other allied healthcare professionals [73, 74, 77–83, 85–91], or guideline implementation [75, 76] in primary healthcare settings. Evidence from poor- to high-quality reviews indicate organizational changes to increase collaboration among pharmacists, nurses, prevention coordinators, and other primary healthcare professionals led to increased physicians’ adherence to guidelines [75].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from poor- to high-quality reviews indicate organizational changes to increase collaboration among pharmacists, nurses, prevention coordinators, and other primary healthcare professionals led to increased physicians’ adherence to guidelines [75]. Nurse-led care was found to be as equally effective as general practitioners in patient satisfaction, asthma, cardiovascular, and diabetes management.…”
Section: Resultsmentioning
confidence: 99%
“…(15) The implementation of strategies can contribute to its adoption in the PHC, improving the quality of care and patient safety. (16) The advance of risk stratification for children, adults, elderly and chronically ill demonstrates that it is possible to classify risk and plan actions, an important aspect to address the trends of the elderly people and the changes in the epidemiological profile of the communities. The incipient results regarding adolescents suggests greater involvement of the school and parents in order to optimize care.…”
Section: Discussionmentioning
confidence: 99%
“…A study assessing official ACC/AHA guidelines found that significant changes in guidelines are common in updated revisions . Other studies have shown that physicians have hesitancy in following newer guidelines, especially upon initiation . Other reasons as to why clinical practice is not guided by the new recommendations include disagreement with the current recommendations and comfort with previous guidelines, including those by the JNC 7.…”
Section: Discussionmentioning
confidence: 99%